마우스형 통합 질감 제시 시스템 개발 - 경기욱; 손승우; 양기훈; 권동수; 김문상 (제어·로봇·시스템학회, 2005)
In this paper, we suggest an integrated tactile display system that provides kinesthetic force, pressure distribution, vibration and slip/stretch. The system consists of two parts: a 2 DOF force feedback device for kinesthetic display and a tactile feedback device for displaying the normal stimulation to the skin and the skin slip/stretch. Psychophysical experiments measure the effects of fingerpad selection, the direction of finger movements and the texture width on tactile sensitivity. We also investigate the characteristics of lateral finger movement while subjects perceive different textures. From the experimental results, the principal parameters for designing a tactile display are suggested. A tactile display device, using eight piezoelectric bimorphs and a linear actuator, is implemented and attached to a 2 DOF translational force feedback device to simultaneously simulate the texture and stiffness of the object. As a result, we find out that the capability of the suggested device is sufficient to display physical quantities to display the texture.